2015
DOI: 10.1515/aoa-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility in Rooms with and without an Induction Loop for Hearing Aid Users

Abstract: The paper presents the results of sentence and logatome speech intelligibility measured in rooms with induction loop for hearing aid users. Two rooms with different acoustic parameters were chosen. Twenty two subjects with mild, moderate and severe hearing impairment using hearing aids took part in the experiment. The intelligibility tests composed of sentences or logatomes were presented to the subjects at fixed measurement points of an enclosure. It was shown that a sentence test is more useful tool for spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…BS8300 regulation in the UK or EN 60118-4 standard) in order to ensure high quality sound for users of hearing aids. The users of assistive listening devices reported that speech intelligibility and general satisfaction with sound perception is efficiently improved in rooms equipped with an induction loop (Kociński, Ozimek 2015). Participants of the line-up sessions who use hearing aids might then simply be asked to switch the hearing aid to T-mode for the induction loop signal receiver.…”
Section: Discussion and Suggestions For Improvementmentioning
confidence: 99%
“…BS8300 regulation in the UK or EN 60118-4 standard) in order to ensure high quality sound for users of hearing aids. The users of assistive listening devices reported that speech intelligibility and general satisfaction with sound perception is efficiently improved in rooms equipped with an induction loop (Kociński, Ozimek 2015). Participants of the line-up sessions who use hearing aids might then simply be asked to switch the hearing aid to T-mode for the induction loop signal receiver.…”
Section: Discussion and Suggestions For Improvementmentioning
confidence: 99%
“…Therefore, for listeners who are predominantly concerned with communication in these environments, listener age and degree of hearing loss (to a lesser extent) may be the best factors with which to infer a listener’s susceptibility to the reverberation. On the other hand, a large church may have a reverberation time as high as 5 seconds (Kociński and Ozimek, 2015). For listeners most concerned with communication in an environment with such severe reverberation, it would be better to consider the listener’s working memory capacity (measured using the RST) and age as clinical predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Sentences were processed and presented at three possible reverberation times: no reverberation (0.0 seconds), moderate reverberation (1.0 seconds), or severe reverberation (4.0 seconds). These three reverberation conditions were selected because they represent the range of reverberant degradation found in the real world (Hodgson et al, 2007; Kociński and Ozimek, 2015). See Figure 2 for an example of the same sentence waveform in each of the three reverberation conditions.…”
Section: Methodsmentioning
confidence: 99%